PERTANGGUNGJAWABAN PIDANA RUMAH SAKIT ATAS TINDAKAN TENAGA KESEHATAN MENURUT UU NO.44 TAHUN 2009 - Hwian Christianto (Fakultas Hukum Universitas Surabaya, 2018)
The Law Number 44, 2009 explicitly regulates that C! hospital must be responsible lawfully of all disadvantages caused by medical crew. It means that the hospital may not reject every law-claims proposed by the customers. This measurement gives protection of law's problem of the patients in one side, and it also intends the hospital to operate more professional. The question is, how far the hospital shall be responsible for all disadvantages. That's why the understanding of corporate responsibility is very important for applying its law measurement. This thing is quite related to the hospital as a corporation, according to its characteristics. The concept oj hospital's criminal-responsibility, could be applied in disadvantages which is caused by itself or by the law protection in itself